Anti-neuroinflammatory effect of 6, 8, 1′-tri-O-methylaverantin, a metabolite from a marine-derived fungal strain Aspergillus sp., via upregulation of heme oxygenase-1 in lipopolysaccharide-activated microglia. (February 2018) - Kim, Kwan-Woo; Kim, Hye Jin; Sohn, Jae Hak; Yim, Joung Han; Kim, Youn-Chul; Oh, Hyuncheol
Abstract: In the course of searching for anti-neuroinflammatory metabolites from marine-derived fungi, three fungal metabolites, 6, 8, 1′-tri- O -methylaverantin, 6, 8-di- O -methylaverufin, and 5-methoxysterigmatocystin were isolated from a marine-derived fungal strain Aspergillus sp. SF-6796. Among these, 6, 8, 1′-tri- O -methylaverantin induced the expression of heme oxygenase (HO)-1 protein in BV2 microglial cells. The induction of HO-1 protein was mediated by the activation of nuclear transcription factor erythroid-2 related factor 2 (Nrf2), and was regulated by the p38 mitogen-activated protein kinase and phosphatidylinositol 3-kinase/protein kinase B signaling pathways. Furthermore, 6, 8, 1′-tri- O -methylaverantin suppressed the overproduction of pro-inflammatory mediators, such as nitric oxide, prostaglandin E2, inducible nitric oxide synthase, and cyclooxygenase-2 in lipopolysaccharide (LPS)-stimulated BV2 microglial cells. These anti-neuroinflammatory effects were mediated through the negative regulation of the nuclear factor kappa B pathway, repressing the phosphorylation and degradation of inhibitor kappa B-α, translocation into the nucleus of p65/p50 heterodimer, and DNA-binding activity of p65 subunit. The anti-neuroinflammatory effect of 6, 8, 1′-tri- O -methylaverantin was partially blocked by a selective HO-1 inhibitor, suggesting that its anti-neuroinflammatory effect is at least partly mediated by HO-1 induction. In this study, 6, 8, 1′-tri- O -methylaverantin also induced HO-1 protein expression in primary microglial cells, and this correlated with anti-neuroinflammatory effects observed in LPS-stimulated primary microglial cells. In conclusion, 6, 8, 1′-tri- O -methylaverantin represents a potential candidate for use in the development of therapeutic agents for the regulation of neuroinflammation in neurodegenerative diseases. Graphical abstract: Highlights: 6, 8, 1′-tri- O -methylaverantin activated Nrf2/HO-1 signaling in BV2 cells. The HO-1 induction was mediated by p38 MAPK and PI3K/Akt cascades. 6, 8, 1′-tri- O -methylaverantin exhibited anti-inflammatory effect in BV2 cells. Similar effects were observed in primary microglial cells.